Congenital Long QT Syndrome: a Systematic Review - Edvard Galić (Acta Clinica Croatica, 2021)
Congenital long QT syndrome (LQTS) is a disorder of myocardial repolarization defined by a prolonged QT interval on electrocardiogram (ECG) that can cause ventricular arrhythmias and lead to sudden cardiac death. LQTS was first described in 1957 and since then its genetic etiology has been researched in many studies, but it is still not fully understood. Depending on the type of monogenic mutation, LQTS is currently divided into 17 subtypes, with LQT1, LQT2, and LQT3 being the most common forms. Based on the results of a prospective study, it is suggested that the real prevalence of congenital LQTS is around 1:2000. Clinical manifestations of congenital LQTS include LQTS-attributable syncope, aborted cardiac arrest, and sudden cardiac death. Many patients with congenital LQTS will remain asymptomatic for life. The initial diagnostic evaluation of congenital LQTS includes obtaining detailed personal and multi-generation family history, physical examination, series of 12-lead ECG recordings, and calculation of the LQTS diagnostic score, called Schwartz score. Patients are also advised to undertake 24-hour ambulatory monitoring, treadmill/cycle stress testing, and LQTS genetic testing for definitive confirmation of the diagnosis. Currently available treatment options include lifestyle modifications, medication therapy with emphasis on betablockers, device therapy and surgical therapy, with beta-blockers being the first-line treatment option, both in symptomatic and asymptomatic patients.